HUBUNGAN POLA ASUH MAKAN TERHADAP STATUS GIZI BALITA USIA 7-59 BULAN - Jeklin Feronika Tolaba; Armenia Eka Putriana; Nency Florence Damanik (JOURNAL HEALTH AND NUTRITIONS, 2022)
The problem of malnutrition can also be seen from the slow growth of the child's height, which is reflected in the length or height. The purpose of this study was to determine the relationship between eating parenting patterns and the nutritional status of children aged 7-59 months in the working area of the Watutau Health Center, Poso Regency. This type of research is analytic observational with a cross sectional approach. The population in this study were all children under five and mothers of children under five in the working area of the Watutau Health Center which amounted to 203 people with purposive sampling technique. The results of this study statistically showed that there was no difference in the relationship between eating patterns and the nutritional status of children under five with a significance value of 0.899. The conclusion in this study is that there is no difference in the relationship between parenting and nutritional status of children under five years old.Masalah kekurangan gizi pun dapat dilihat dari lambatnya proses pertumbuhan tinggi badan anak yang tercermin dari panjang atau tinggi badan. Tujuan penelitian ini adalah mengetahui hubungan pola asuh makan terhadap status gizi balita usia 7-59 bulan di wilayah kerja Puskesmas Watutau Kabupaten Poso. Jenis penelitian ini adalah observasional analitik  dengan pendekatan cross sectional. Populasi dalam penelitian ini seluruh balita dan ibu balita di wilayah kerja Puskesmas Watutau yang berjumlah 203 orang dengan tehnik pengambilan sampel purposive sampling. Hasil penelitian ini secara statistik menunjukkan tidak ada perbedaan hubungan pola asuh makan dan status gizi balita dengan nilai Signifikansi 0,899. Kesimpulan pada penelitian ini adalah tidak ada perbedaan hubungan pola asuh makan dan status gizi balita.